METABOLIC SYNDROME AND RISK OF CARDIOVASCULAR DISEASE WITH THYROID DISORDER - RAVI SHANKAR; NEHA SHARMA; AJAY KUMAR; RAJU RAM; APARAJITA KUSHWAHA (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: Metabolic syndrome (MetS) is the most widely used term for the aggregation of metabolic abnormalities, which leads to an increase in the risk of developing cardiovascular pathology. The prevalence of MetS is increasing all over the world with distinct evidence of high prevalence in India and other South Asian countries. Thyroid dysfunction, prominently subclinical hypothyroidism, has been observed more frequently in patients of MetS than in the general population. Methods: This cross-sectional, observational study was conducted among MetS patients in the general population and near and dear of patients (350) at the Pacific Institute of Medical Sciences, Udaipur. For the determination of gastric peptidases (ghrelin and obestatin), insulin was done by enzyme-linked immunosorbent assay. Thyroid hormones are determined by chemiluminescence. Results: The key findings in this analysis are the significant negative correlation between insulin and ghrelin. This inverse relationship was observed in individuals without cardiovascular disease (CVD), suggesting that even in the absence of overt CVD, insulin may play a role in regulating ghrelin levels. This finding is particularly noteworthy given ghrelin’s role in appetite regulation and energy balance. Conclusion: The findings emphasize the need for a holistic approach to health assessment and management, considering individual factors such as age, sex, and the presence of underlying health conditions along with thyroid disorders.